Tahap penggunaan media (TV Pendidikan) dalam proses pengajaran dan pembelajaran di kalangan guru-guru sekolah rendah - Aida Kertina, Hamden Hamid (2010)
The purpose of this research is to identify the usage level of Media (Educational TV) in the teaching and learning processes among primary school teachers. The research also aims to identify the constraints faced and suggestions for improvement in schools, Teachers Resource Centres and the State Education Technology Division to further enhance the usage of Educational TV in teaching and learning. For this study, a sample of 200 primary schools teachers teaching year 3, 4 and 5 from 10 primary schools in the Kuching North District (5 urban primary schools and 5 rural primary schools) were selected using purposive sampling. Data for the study was collected through questionnaires and analysed using descriptive and inferential statistics. Instructional Materials Motivational Scales (IMMS) of Keller (1986) modified by Toh & Fattawi (2001) was used to measure the usage level of Educational TV. The findings indicate that the usage level of Educational TV was low, that is, at least one program was used once in a year. Bahasa Melayu and Science program have the highest usage. The perception of urban and rural teachers toward Educational TV program 'in teaching and learning was high. The findings also indicate that there was no significant difference among urban and rural teachers in the usage frequency of Educational TV in teaching and learning with on air program and recorded program. There was no significant difference in the perception among male and female teachers with respect to whether the synopsis in the table was of help to teachers in the preparation for the teaching and learning using Educational TV program. There was also both significant and non significant relationship between the usage of Educational TV program based on subjects in the teaching and learning processes and the perception of teachers in the category of teaching of Educational TV to enhance the students'comprehension of the subjects.